Review on Anti-Biofilm Potential of CRISPR-Cas System on Various Pathogens: Life Sciences -Biotechnology - Chakraborty, Tamalika; Chatterjee, Sumana; Datta, Lopamudra; Shaw, Ranjana (International Journal of Life Science and Pharma Research, 2023)
The development of bacterial biofilms entails regulatory as well as signalling mechanisms that regulate the shift from a mobile to astationary state of existence, the production of the extracellular polymeric matrix, and the progression of 3-dimensional biofilm formation withemphasis on how easily they may be created and how crucial they are in biological, ecological, and industrial settings, biofilms are the subject ofextensive research. Biofilms and a variety of pathogenic human disorders are frequently linked. Since bacteria in biofilms can resist antibiotics, theimmune system, and other treatments, biofilm infections are typically long-lasting. Many prokaryotes include CRISPR-associated proteins (Cas), a solidadaptable immunological system that may be programmed to damage the bacterial genomes and induce cell death. Short palindromic repeats that aregrouped and adequately spaced together make up CRISPR-Cas. In light of this, CRISPR-Cas can be seen as an exciting strategy to address andovercome antibiotic resistance. Furthermore, the CRISPR-Cas system can create "precise antimicrobials" that target bacterial infections according tospecific DNA sequences. This CRISPR-Cas technique is susceptible to drug-resistant microorganisms due to its selective targeting of the genesinvolved in biofilm formation, pathogenicity, and antibiotic resistance. However, this method requires potent vectors for the CRISPR-Cas system toaccess the bacterial genomes. As vectors, genetically engineered Phage, liposomes, and lipid-mediated nanoparticles are exciting options. Thistechnique has been used to prevent extracellular and intracellular from forming biofilms. The most current developments in creating innovations andpossible advantages of the various CRISPR-Cas delivery methods for the deliberate eradication of bacterial pathogens will be covered in this review,focussing mainly on the anti-biofilm potential, which is found to be one of the primary causes of the difficulty of irradiation of Multi-drug resistantbacteria. Additionally, each distribution system’s positive aspects are highlighted, along with its challenges and potential for advancement in the future.